TRIM56 Modulates YBX1 Degradation to Ameliorate ZBP1‐Mediated Neuronal PANoptosis in Spinal Cord Injury - Junsheng Lou; Yiting Mao; Wu Jiang; Honghao Shen; Yunpeng Fan; Qing Yu; Conghui Zhou; Ziyao Wei; Kailiang Zhou; Mengran Jin; Junsong Wu (Advanced Science, 2024)
Abstract Spinal cord injury (SCI) is a severe injury to the central nervous system, and its treatment is always a major medical challenge. Proinflammatory cell death is considered an important factor affecting neuroinflammation and the prognosis after injury. PANoptosis, a newly discovered type of proinflammatory cell death, regulates the activation of executioner molecules of apoptosis, pyroptosis and necroptosis through the PANoptosome, providing a new target for therapeutic intervention after SCI. However, its role and regulatory mechanism in SCI are not yet elucidated. Here, based on proteomic data, YBX1 expression is significantly increased in neurons after SCI. Guided by RIP‐seq, subsequent experiments reveal that YBX1 promotes ZBP1 expression by stabilizing the Zbp1 mRNA, thereby aggravating ZBP1‐mediated PANoptosis. Furthermore, the E3 ubiquitin ligase TRIM56 is identified as an endogenous inhibitor of YBX1 via molecular docking and IP/MS analysis. Mechanistically, TRIM56 bound to YBX1 and promoted its ubiquitination, thereby accelerating its degradation. Taken together, these findings reveal a novel function of YBX1 in regulating ZBP1‐mediated PANoptosis in the pathogenesis of SCI and verified that TRIM56 functions as an endogenous inhibitor to promote the ubiquitin‐proteasomal degradation of YBX1, providing new insights into SCI treatment strategies.